IN SILICO MOLECULAR DOCKING STUDIES OF COUMARIN-CHALCONE HYBRIDS AGAINST SARS-COV-2 MAIN PROTEASE (6LU7) - Sathish K. Konidala; Vijay Kotra
The present work aimed to explore efficient lead molecules to combat against COVID-19. Despite the extensive usage of repurposed medications for COVID-19 therapy due to their inadequacy to proper control of endangered pandemic, there is an urgent need to discover innovative compounds that are very effective against the COVID-19 pandemic. Newly synthesized coumarin-chalcone hybrids were assessed for their efficacy to inhibit main protease 6LU7(Mpro) and compared it with some repurposing COVID-19 drug activity through in silico technique. Among all synthesized hybrids, d11, a11, c12, b11 and c5, showed highest binding affinities with the least docking score against protease (PDB ID: 6LU7) protein comparable to repurposed drugs currently used against COVID-19. The selected hybrids having coumarin, chalcone, and dihydropyridine pharmacophores are promising for their anti-COVID-19 activity. However, further extensive research is required through suitable in vitro and in vivo methods.